Infinite-Layer Nickelate Superconductors: A Current Experimental Perspective of the Crystal and Electronic Structures - Chow, L. E.; Ariando, A. (Frontiers in Physics, 2022)
After the reward of more than two decades of pursuit on the high-Tc cuprate analog with the hope to obtain a better understanding of the mechanism of high-Tc superconductivity, the discovery of superconductivity in the infinite-layer nickelate brings more mystery to the picture than expected. Tops in the list of questions are perhaps (1) absence of superconductivity in the bulk nickelate and limited thickness of the infinite-layer phase in thin film, (2) absence of superconductivity in the La-nickelate despite it being the earliest studied rare-earth nickelate, and the role of 4𝑓 orbital in the recipe of superconductivity, (3) absence of Meissner effect and suspect of the origin of superconductivity from the interface, (4) whether nickelate hosts similar pairing symmetry to the single-band high-Tc cuprates or multiband iron-based superconductor. In this perspective article, we will discuss the following aspects: (1) stabilization of the infinite-layer phase on the SrTiO3(001) substrate and the thickness dependency of observables; (2) rare earth dependence of the superconducting dome and phase diagram on the (La/Pr/Nd)- infinite-layer nickelate thin film; (3) experimental aspects of the measurement of Meissner effect; (4) theoretical framework and experimental study of the pairing symmetry of infinite-layer nickelate superconductor.